2018
DOI: 10.1007/s11095-018-2445-y
|View full text |Cite
|
Sign up to set email alerts
|

Fampridine is a Substrate and Inhibitor of Human OCT2, but not of Human MATE1, or MATE2K

Abstract: The studies indicated fampridine is a substrate and inhibitor of OCT2, but not MATE1 or MATE2K. Results from the study suggested the active renal secretion of fampridine is mediated by human OCT2 but not MATE1 or MATE2K. To our knowledge, fampridine is the first reported substrate specific to OCT2 but not to MATE1 or MATE2K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Most of the inhibitors for renal transporters OCT2 and MATE1 or MATE2K are overlapped, although relatively specific inhibitors for MATE1 and MATE2K such as famotidine, nizatidine and pyrimethamine, and relatively specific inhibitors for OCT2 such as disopyramide, have been identified ( 25 29 ). In this paper, we report that ulotaront is an inhibitor of OCT2 but not MATE1 or MATE2K (Figure S 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the inhibitors for renal transporters OCT2 and MATE1 or MATE2K are overlapped, although relatively specific inhibitors for MATE1 and MATE2K such as famotidine, nizatidine and pyrimethamine, and relatively specific inhibitors for OCT2 such as disopyramide, have been identified ( 25 29 ). In this paper, we report that ulotaront is an inhibitor of OCT2 but not MATE1 or MATE2K (Figure S 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…To clarify whether inhibition of mCAT-1 or Oct-2 activity can relieve E. piscicida infection-induced NLRP3 inflammasome inhibition, we assessed the ability of specific inhibitors that target mCAT-1 (cyclosporine) (Grupper et al, 2013) or Oct-2 (cimetidine) (Xiao et al, 2018) and found that pretreatment of nlrc4 À/À BMDMs with cyclosporine or cimetidine can result in significantly elevated markers of NLRP3 inflammasome activation, including LDH release (Figure 3C), IL-1b secretion (Figure 3D), and caspase-1 activation (Figure 3E), compared with wild-type E. piscicida-infected macrophages (Figures 3C-3E).…”
Section: E Piscicida Converts Host Cytosolic Arginine Into Spermine mentioning
confidence: 99%